SPATIAL DISTRIBUTION AND POTENTIALS OF ECOTOURISM RESOURCES IN KANO STATE, NIGERIA - Shu’aibu Muhammad, Aliyu; Uba Muhammadu, Murtala; Ahmed, Muhammad (African Journal of Social and Behavioural Sciences, 2024)
This study examines the geospatial distribution of 51 major ecotourism resources in Kano. The coordinates of the ecotourism resources were collected via the hand- held Global Positioning System Garmin eTrex H and the data obtained were related to their geographical locations and attributes. Data pertaining to the potential of ecotourism resources were collected via a checklist, interviews and observations at each site and were analysed via SPSS version 17.0. The results of the analyses indicate that the spatial pattern of ecotourism resources is a dispersed pattern and that most ecotourism resources are very poor owing to the locational characteristics of rural areas where limited infrastructure development has occurred. The provision of adequate facilities through public-private partnerships at each destination should be encouraged by incentivizing rural people to establish the facilities needed for the promotion of ecotourism and the provision of adequate and qualitative road networks that make a site more attractive.